2000
DOI: 10.1128/.38.6.2156-2161.2000
|View full text |Cite
|
Sign up to set email alerts
|

A Filamentous Phage Associated with Recent PandemicVibrio parahaemolyticus O3:K6 Strains

Abstract: A specific serotype, O3:K6, of Vibrio parahaemolyticus has recently been causing epidemics of gastroenteritis in Southeast Asia, Japan, and North America. To examine whether the new O3:K6 strains possess characteristics that may exacerbate outbreaks, we compared V. parahaemolyticus O3:K6 strains with non-O3:K6 strains using strains isolated from individuals with traveler's diarrhea at Kansai Airport Quarantine Station, Osaka, Japan. All 24 O3:K6 strains possessed a common plasmid, pO3K6 (DNA size, 8,782 bp, wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
101
1
2

Year Published

2000
2000
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(104 citation statements)
references
References 22 publications
0
101
1
2
Order By: Relevance
“…Phylotypes clustering within the genus Vibrio were present in most of the samples, showing low (3.5%) to moderate (19.0%) relative abundance. The majority of their closest relatives originated from marine animals (Nasu et al, 2000;Nishiguchi & Nair, 2003;Jensen et al, 2009). This genus is often found in associations with the gut of marine animals varying from parasitism to mutualism and showing diverse metabolic capabilities (Thompson et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Phylotypes clustering within the genus Vibrio were present in most of the samples, showing low (3.5%) to moderate (19.0%) relative abundance. The majority of their closest relatives originated from marine animals (Nasu et al, 2000;Nishiguchi & Nair, 2003;Jensen et al, 2009). This genus is often found in associations with the gut of marine animals varying from parasitism to mutualism and showing diverse metabolic capabilities (Thompson et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have examined the diversity of vibriophages associated with Vibrios isolated from coastal environments (Chang et al, , 2002Nasu et al, 2000;Miller et al, 2003;Seguritan et al, 2003), and a few studies have determined the diversity and distribution of plasmids among environmental Vibrios (Shehane & Sizemore, 2002;Roig & Amaro, 2009). In a previous study, we characterized three plasmids isolated from diverse environmental Vibrios including V. mediterranei, V. campbellii, and V. fluvialis .…”
Section: Mges Facilitate the Expansion Of The Vibrio Ecological Nichementioning
confidence: 99%
“…The additional fragments of KX-V226 may be derived from the RF of a Vf33-like phage because a band corresponding to an extrachromosomal DNA of about 8.5 kb in size was detected only in this strain when the undigested total cellular DNAs of the pandemic strains were hybridized with the Vf33 DNA (data not shown). During the course of our study, Nasu et al [17] reported a 8782-bp plasmid present in the pandemic O3:K6 strain isolated at the quarantine station in Japan is the RF DNA of a Vf33-like ¢lamentous phage (designated as f237). The hybridization pro¢le shared by most pandemic strains was di¡erent from those of other test strains.…”
Section: Restriction Fragment Length Polymorphism Of the Vf33 Dna-likmentioning
confidence: 80%
“…1). Nasu et al [17] reported that an orf8 gene located on the morphogenesis region of f237 may be associated with virulence of the pandemic strains. Therefore, the nucleotide sequence of the morphogenesis region in the pandemic strains may encode the virulence function or survival function.…”
Section: Restriction Fragment Length Polymorphism Of the Vf33 Dna-likmentioning
confidence: 99%